A Meta-Analytic Study on Audit Fees and Audit Quality in Indonesia - Suwarno, Try Edi; Laoli, Victorinus; Prabowo, Kristianto Tricahya; Rizka, Nor Rahma; Ulfida, Deafatunnizwa (Quantitative Economics and Management Studies, 2025)
Numerous studies on audit quality have been conducted, and one of the factors influencing audit quality is audit fees. This study employs a meta-analysis method with a correlation approach to examine the relationship between audit fees and audit quality. The author reviewed 100 journals relevant to the topic of audit fees and audit quality over the past five years, utilizing Publish or Perish. These journals were selected based on specific eligibility criteria and analyzed using JASP software. The results indicate a z-value of 8.029 and a p-value < 0.001, which is smaller than the 5% (0.05) significance level. This finding demonstrates a significant positive correlation between audit fees and audit quality, although the effect size is relatively low (rRE = 0.211). Therefore, while audit fees are positively and significantly associated with audit quality, the strength of the correlation remains low. Based on these findings, the researcher recommends that companies consider paying higher audit fees to enhance the quality of audits obtained.